Review of the subgenus Tachycines (Gymnaeta) Adelung, 1902 (Orthoptera, Rhaphidophoridae, Aemodogryllinae, Aemodogryllini) - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2019)
In this work, ten new species of Tachycines (Gymnaeta) are identified and described from China: Tachycines (Gymnaeta) parvus sp. nov., Tachycines (Gymnaeta) lushuicus sp. nov., Tachycines (Gymnaeta) yueyangensis sp. nov., Tachycines (Gymnaeta) lii sp. nov., Tachycines (Gymnaeta) dianxicus sp. nov., Tachycines (Gymnaeta) pallidus sp. nov., Tachycines (Gymnaeta) dispar sp. nov., Tachycines (Gymnaeta) verus sp. nov., Tachycines (Gymnaeta) vicinus sp. nov., Tachycines (Gymnaeta) maoershanensis sp. nov.. Two subspecies of Gorochov et al. (2006): T. (G.) ferecaecus ferecaecus (Gorochov, Rampini & Di Russo, 2006) and T. (G.) ferecaecus proximus (Gorochov, Rampini & Di Russo, 2006) are elevated as two independent valid species. Also two subspecies of Gorochov (2010): T. (G.) sichuanus sichuanus (Gorochov, 2010) and T. (G.) sichuanus altimontanus (Gorochov, 2010) can be elevated as two independent species. Three synonyms: Tachycines (Gymnaeta) tianmushanensis Liu & Zhang, 2001 syn. n., Tachycines (Gymnaeta) improvisus (Gorochov, 2010) syn. n. and T. (G.) aspes (Rampini, Di Russo & Cobolli, 2008) syn. n. are proposed. A new combination Eutachycines crenatus (Gorochov, Rampini & Di Russo, 2006) comb. nov. is involved. A key to the species of Tachycines (Gymnaeta) is provided.